Differences in reef fish assemblages between populated and remote reefs spanning multiple archipelagos across the central and western Pacific - Williams, I.; Richards, B.; Sandin, S.; Baum, J.; Schroeder, R.; Nadon, M.; Zgliczynski, B.; Craig, P.; McIlwain, Jennifer; Brainard, R. (Hindawi Publishing Corporation, 2011)
Comparable information on the status of natural resources across large geographic and human impact scales provides invaluable context to ecosystem-based management and insights into processes driving differences among areas. Data on fish assemblages at 39 US flag coral reef-areas distributed across the Pacific are presented. Total reef fish biomass varied by more than an order of magnitude: lowest at densely-populated islands and highest on reefs distant from human populations. Remote reefs (<50 people within 100 km) averaged ~4 times the biomass of “all fishes” and 15 times the biomass of piscivores compared to reefs near populated areas. Greatest within-archipelagic differences were found in Hawaiian and Mariana Archipelagos, where differences were consistent with, but likely not exclusively driven by, higher fishing pressure around populated areas. Results highlight the importance of the extremely remote reefs now contained within the system of Pacific Marine National Monuments as ecological reference areas.